Modified asphalt composition, preparation method and application thereof, and modified asphalt waterproof coiled material
By dipping the modified asphalt composition in the polyester tire to form a three-dimensional network structure, the problem of shrinking and deformation of traditional waterproof coils at extremely low temperatures is solved, and the anti-deformation and anti-aging performance of the modified asphalt waterproof coils are improved.
Patent Information
- Application Number
- CN202411908174.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Traditional asphalt waterproof coils are prone to shrinkage and deformation in extremely low temperature environments, resulting in damage and leakage of overlapping sides, and excessive reserved margin increases production costs.
Using a modified asphalt composition, a three-dimensional network structure is formed by dipping the asphalt, nanosilica, carbon nanotubes, asphalt mastidium and hydrogenated styrene-butadiene block copolymer with different needle insertions in the polyester tire to form a three-dimensional network structure, which enhances the anti-deformation and anti-aging properties of the waterproof coil.
The modified asphalt waterproof coil maintains good dimensional stability at extremely low temperatures, reducing shrinkage and deformation, extending service life, and reducing production costs.
Smart Images

Figure BDA0005206258950000241 
Figure HDA0005206259100000011 
Figure HDA0005206259100000012
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of building waterproof materials, and in particular relates to a modified asphalt composition, a preparation method thereof, a use thereof, and a modified asphalt waterproofing membrane. Background Art
[0002] Shrinkage and deformation of waterproofing membranes is a relatively important problem faced in waterproofing projects. At present, in order to deal with the situation that the area of waterproofing membranes may not meet the standards after shrinkage, and to ensure that the use area of waterproofing membranes in different use environments meets national standards, manufacturers usually reserve a certain margin during the production process, that is, use an over-wide tire body and lengthen the length of the membrane. For example, for a 10-square-meter waterproofing membrane, a polyester tire with a width of 1015 mm is generally selected as the tire body of the waterproofing membrane, and the production length of the waterproofing membrane is set to 1020 cm. However, although the problem of reserved margins has been considered and margin design has been made during production, when these waterproofing membranes are used in extremely low temperature environments, the waterproofing membranes will still shrink significantly, which will cause the overlap edges of the waterproofing membranes to be damaged and cause leakage. This not only poses a great challenge to the waterproofing performance of buildings, but also forces people to re-examine the limitations of traditional asphalt waterproofing membranes in dealing with special environments. For example, in extremely low temperatures or severe cold climates, how to effectively solve the shrinkage problem of waterproofing membranes and ensure the firmness of the overlap edges has become a difficult problem in the field of waterproofing projects. Moreover, excessive excess also brings heavy cost burden to manufacturers. Excessive width of carcass and extended coil length mean more raw material input, from carcass material procurement to energy consumption in the production process, to increased storage and transportation costs, each link accumulates high cost expenditure due to excessive excess.
[0003] For the problem of shrinkage and deformation of waterproof coiled materials, the prior art discloses that the two sides of the polyester tire carcass layer are respectively coated with anti-deformation filling layers, so as to make the waterproof coiled materials have anti-deformation ability by using the anti-deformation filling layers. The prior art also discloses an anti-deformation thermoplastic polyolefin waterproof coiled material, which is prepared by a high-intensity mechanical method with nitrile composite rubber particles embedded with graphene oxide, and the island structure thereof makes the coiled material not easy to deform while being highly flexible; the nitrile composite rubber particles are dispersed in a polypropylene matrix, and a supporting structure is formed with graphene through dynamic vulcanization to improve the strength of the coiled material; the graphene oxide modified by bis(trimethoxysilylethyl)benzene is polymerized with 3-aminopropylmethyldimethoxysilane to form an aminated and hyperbranched polysiloxane structure, which realizes chemical cross-linking with the plastic layer, improves its anti-deformation effect, and can also replace polyvinyl chloride to absorb ultraviolet rays, and synergistically improve the anti-aging effect with the amine group. The above two methods are relatively complex in structure during the production process, and the latter has a relatively high production cost, too long insulation time, and too high energy consumption. Summary of the invention
[0004] The embodiments of the present application provide a modified asphalt composition, a preparation method thereof, a use thereof, and a modified asphalt waterproofing membrane, which can make the prepared modified asphalt waterproofing membrane have the effects of anti-deformation, anti-aging, and waterproofing.
[0005] In the first aspect, the present application provides a modified asphalt composition, which is made from the following raw materials with added percentages: first component asphalt, 100PHR; second component asphalt, 60PHR~80PHR; temperature-resistant powder, 10PHR~20PHR; carbon nanotubes, 4PHR~8PHR; asphalt mastic, 4PHR~8PHR; hydrogenated styrene-butadiene block copolymer, 3PHR~7PHR.
[0006] According to the embodiment of the first aspect of the present application, the first component asphalt uses asphalt with a needle penetration of 60 to 110, and the second component asphalt uses asphalt with a needle penetration of 0 to 40; the unit of needle penetration is 1 / 10 mm.
[0007] According to an embodiment of the first aspect of the present application, the temperature-resistant powder is selected from one or a combination of nano-silicon dioxide, sandstone particles, talcum powder, limestone powder, and fly ash.
[0008] According to the embodiment of the first aspect of the present application, the average particle size of sandstone particles, talcum powder and limestone powder is 0.0525-0.25 mm.
[0009] According to an embodiment of the first aspect of the present application, the average particle size of the fly ash is 0.1 μm to 100 μm.
[0010] According to an embodiment of the first aspect of the present application, the average particle size of nano-silicon dioxide is 1 nm to 10 μm.
[0011] According to an embodiment of the first aspect of the present application, the nano-silicon dioxide is gas-phase nano-silicon dioxide.
[0012] According to an embodiment of the first aspect of the present application, the average particle size of the gas-phase nano-silica is 7nm to 500nm.
[0013] According to an embodiment of the first aspect of the present application, the carbon nanotubes are multi-walled carbon nanotubes, the average diameter of the carbon nanotubes is 2 nm to 20 nm, and the axial length of the carbon nanotubes is 5 μm to 15 μm.
[0014] According to an embodiment of the first aspect of the present application, the aspect ratio of the carbon nanotubes is 140-7500.
[0015] According to the embodiment of the first aspect of the present application, the bonding strength of asphalt mastic at 20°C is 1.4 kg / cm 2 ~1.6kg / cm 2The frost resistance requires no cracking or detachment when hung at -40℃ for 2 hours, and the elongation at 25℃ is 35cm~45cm.
[0016] According to an embodiment of the first aspect of the present application, asphalt mastic is prepared from 8% to 10% of 1 mm coarse aggregate, 25% to 30% of 200 mesh mineral powder, 45% to 60% of asphalt with a needle penetration of 60 to 110, and 2.5% to 3% of fiber stabilizer; wherein the unit of needle penetration is 1 / 10 mm.
[0017] According to the embodiment of the first aspect of the present application, the hydrogenated styrene-butadiene block copolymer is a linear or star-shaped structure or a combination thereof, the molecular weight of the hydrogenated styrene-butadiene block copolymer is 150,000 to 450,000, and the mass content of the styrene segment in the hydrogenated styrene-butadiene block copolymer is 25% to 35%.
[0018] In the second aspect, the present application provides a method for preparing a modified asphalt composition, comprising: dispersing a first component asphalt and a second component asphalt according to the ratio of the modified asphalt composition, heating the temperature to 120°C to 140°C to melt the first component asphalt and the second component asphalt to obtain an asphalt dispersion raw material; adding asphalt mastic and hydrogenated styrene-butadiene block copolymer to the asphalt dispersion raw material for dispersion, and heating the temperature to 160°C to 180°C for insulation treatment to obtain a polymer asphalt dispersion; adding temperature-resistant powder and carbon nanotubes to the polymer asphalt dispersion, and heating the temperature to 180°C to 190°C to obtain a modified asphalt composition.
[0019] In a third aspect, the present application provides an asphalt waterproofing membrane, comprising: a polyester base, the polyester base is dipped in the above-mentioned modified asphalt composition; a coating layer, at least arranged on one side of the two opposite sides of the polyester base dipped in the modified asphalt composition.
[0020] According to an embodiment of the third aspect of the present application, based on the polyester tire per square meter, the amount of the modified asphalt composition dipped per square meter of the polyester tire is 0.4kg to 1.5kg.
[0021] According to an embodiment of the third aspect of the present application, the polyester tire is a reinforced polyester tire.
[0022] According to an embodiment of the third aspect of the present application, the coating layer is a coating composition composed of the following components in percentage by mass: 70# asphalt, 45% to 55%; softening oil, 12% to 14%; SBS modifier, 5% to 7%; tire rubber powder, 8% to 11%; filler, 20% to 30%.
[0023] According to an embodiment of the third aspect of the present application, the modified asphalt waterproof membrane further includes an isolation protective layer, which covers the surface of the coating layer on one side facing away from the polyester base.
[0024] According to an embodiment of the third aspect of the present application, the isolation protective layer is made of transparent PE material.
[0025] According to an embodiment of the third aspect of the present application, the SBS modifier is a styrene-butadiene-styrene block copolymer, the molecular weight of which is 150,000 to 400,000, and the mass content of the styrene segment is 20% to 30%.
[0026] According to an embodiment of the third aspect of the present application, the average particle size of the tire rubber powder is 70 mesh to 120 mesh.
[0027] According to an embodiment of the third aspect of the present application, the filler is selected from stone powder, heavy calcium powder, fly ash or a combination thereof.
[0028] According to an embodiment of the third aspect of the present application, the average particle size of the filler is 180 mesh to 300 mesh.
[0029] In the fourth aspect, the present application provides a method for preparing a modified asphalt waterproofing membrane, comprising: impregnating a polyester base in a modified asphalt composition that resists shrinkage and deformation at a temperature of 175°C to 185°C to obtain an impregnated polyester base; and coating the coating composition on the impregnated polyester base to obtain a modified asphalt waterproofing membrane.
[0030] In a fifth aspect, the application provides a use of the above-mentioned modified asphalt composition in the preparation of modified asphalt waterproofing membrane.
[0031] The modified asphalt composition of the embodiment of the present application uses a mixture of the first component asphalt and the second component asphalt as a carrier, and incorporates temperature-resistant powder, carbon nanotubes, asphalt mastic, hydrogenated styrene-butadiene block copolymers, which are materials with high toughness and deformation resistance, to form a modified asphalt composition composed of macromolecular compounds connected by repeating units, as a dipping liquid for polyester tires, to be used for modified polyester tires, so that the tiny gaps inside the asphalt molecules are filled with the modified asphalt composition, and a three-dimensional network structure is formed inside. At the same time, the modified asphalt composition containing temperature-resistant powder can also fill the gaps between polyester tires, enhancing the ability of polyester tires to resist deformation at high and low temperatures. When the polyester tire carcass is subjected to deformation external forces such as stretching or compression, the three-dimensional network structure can effectively disperse stress, thereby enhancing the deformation resistance of the polyester tire. In addition, asphalt mastic and hydrogenated styrene-butadiene block copolymers can also optimize the rheological properties of asphalt, and keep the asphalt in good anti-deformation performance under different pressure and temperature conditions. For example, in an environment with large temperature fluctuations, a modified asphalt composition containing hydrogenated styrene-butadiene block copolymer can effectively prevent excessive deformation caused by thermal expansion and contraction of the waterproof membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solution of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0033] Figure 1 It is a schematic flow chart of the method for preparing the modified asphalt composition provided in the examples of the present application.
[0034] Figure 2 It is a schematic diagram of the structure of the modified asphalt waterproof membrane provided in the embodiment of the present application.
[0035] Explanation of the accompanying drawings: 1. Polyester tire; 2. Polyester fiber; 3. Modified asphalt composition; 4. Coating layer; 5. Isolation protection layer; 6. Carbon nanotube. DETAILED DESCRIPTION
[0036] The features and exemplary embodiments of various aspects of the present application will be described in detail below. In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present application, rather than to limit the present application. For those skilled in the art, the present application can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present application by illustrating the examples of the present application.
[0037] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0038] The waterproofing coiled material may shrink partially or as a whole during use, causing the coiled material to peel off from the base layer, or cracks in the coiled material itself. For example, in an environment with large temperature changes, the phenomenon of thermal expansion and contraction is obvious, and some types of waterproofing coiled materials shrink because they cannot adapt to such temperature changes. In the process of improving the prior art, the inventors of this application found that there are two reasons for the shrinkage of waterproofing coiled materials: on the one hand, the characteristics of the waterproofing coiled material itself are the key factors. If the waterproofing coiled material has poor flexibility and low elastic recovery ability, it is easy to shrink and deform. For example, some inferior asphalt waterproofing coiled materials soften and flow at high temperatures, and shrink and harden after cooling. On the other hand, the construction process also has a certain influence on the shrinkage and deformation of the waterproofing coiled material. For example, if there is no expansion space reserved when the waterproofing coiled material is laid, or after hot-melt welding, it will cause shrinkage and deformation. This shrinkage and deformation will reduce the waterproofing effect of the waterproofing coiled material, and in severe cases may cause leakage, so that the waterproofing system of the building is damaged.
[0039] In order to solve the problems of the prior art, the embodiments of the present application provide a modified asphalt composition and a preparation method, use and a modified asphalt waterproofing membrane. The modified asphalt composition provided in the embodiments of the present application is first introduced below.
[0040] In the first aspect, the present application provides a modified asphalt composition, which is made from the following raw materials with added percentages: first component asphalt, 100PHR; second component asphalt, 60PHR~80PHR; nano-silicon dioxide, 10PHR~20PHR; temperature-resistant powder, 4PHR~8PHR; asphalt mastic, 4PHR~8PHR; hydrogenated styrene-butadiene block copolymer, 3PHR~7PHR.
[0041] The modified asphalt composition of the embodiment of the present application uses a mixture of the first component asphalt and the second component asphalt as a carrier, and incorporates temperature-resistant powder, carbon nanotubes, asphalt mastic, hydrogenated styrene-butadiene block copolymers, which are highly tough and resistant to deformation, to form a modified asphalt composition composed of macromolecular compounds connected by repeating units, as a dipping liquid for polyester tires, to be used for modified polyester tires, so that the tiny gaps inside the asphalt molecules are filled with the modified asphalt composition, and a three-dimensional network structure is formed inside. When the polyester tire carcass is subjected to deformation external forces such as tension or compression, the three-dimensional network structure can effectively disperse the stress and enhance the anti-deformation ability of the polyester tire. At the same time, the modified asphalt composition containing anti-temperature powder can also fill the gaps between polyester tires, enhancing the ability of polyester tires to resist deformation at high and low temperatures. In addition, asphalt mastic and hydrogenated styrene-butadiene block copolymers can also optimize the rheological properties of asphalt, and keep the asphalt in good anti-deformation performance under different pressure and temperature conditions. For example, in an environment with large temperature fluctuations, a modified asphalt composition containing hydrogenated styrene-butadiene block copolymer can effectively prevent excessive deformation caused by thermal expansion and contraction of the waterproof membrane.
[0042] In the modified asphalt composition of the embodiment of the present application, mastic asphalt, hydrogenated styrene-butadiene block copolymer, nano-silica and carbon nanotubes can effectively improve the problem of easy shrinkage and deformation of the polyester tire under stress, not only providing the main support force for the modified asphalt waterproof membrane, but also improving the oil permeability, water impermeability, mass increase after immersion and other performance indicators of the modified asphalt waterproof membrane product from the aspect of the modified polyester tire body, effectively improving the quality and extending the service life of the modified asphalt waterproof membrane product.
[0043] In some embodiments of the present application, the viscosity of the modified asphalt composition at 60° C. is 500 Pa·s to 1000 Pa·s. The viscosity of the modified asphalt composition can be measured using a Brookfield viscometer method.
[0044] In some embodiments of the present application, the first component asphalt is selected from asphalt with a needle penetration of 60 to 110, and the second component asphalt is selected from asphalt with a needle penetration of 0 to 40, wherein the unit of needle penetration is 1 / 10 mm.
[0045] For example, the first component asphalt is 70# asphalt, and its penetration is 60-80 1 / 10 mm; the second component asphalt is 30# asphalt, and its penetration is 20-40 1 / 10 mm. The asphalt dispersion raw material is composed of 70# asphalt and 30# asphalt, wherein 30# asphalt is used as asphalt mixed oil. In the process of using 30# asphalt to prepare the modified asphalt composition, its addition amount has little effect on the deformation resistance of the modified asphalt waterproofing membrane.
[0046] In other embodiments, the first component is 100# asphalt, whose penetration is 90-110 1 / 10 mm; the second component asphalt is 10# asphalt, whose penetration is 0-20 1 / 10 mm. The asphalt dispersion raw material is composed of 100# asphalt and 10# asphalt, wherein 10# asphalt is used as asphalt mixed oil. It is understandable that one or more of the grades of 70#-100# asphalt with a penetration of 60-110 1 / 10 mm can also be selected as the first asphalt component, and one or more of the grades of 10#-30# asphalt with a penetration of 0-40 1 / 10 mm can be selected as the second asphalt component to prepare the asphalt dispersion raw material. The smaller the penetration value of the asphalt, the harder the asphalt, the greater the viscosity, and the stronger the ability to resist shear deformation. 1 / 10 mm is the unit of penetration.
[0047] In some embodiments of the present application, the temperature-resistant powder is selected from one or a combination of nano-silicon dioxide, sandstone particles, talcum powder, limestone powder, and fly ash. The temperature-resistant powder of the embodiments of the present application is insensitive to high temperature and extreme low temperature, has small deformation at high temperature or low temperature, is dispersed in the modified asphalt composition, can effectively fill the gaps between asphalt molecules, resist the deformation of the modified asphalt composition caused by high temperature expansion, and the deformation caused by contraction at extreme low temperature.
[0048] In some embodiments of the present application, the average particle size of sandstone particles, talcum powder, and limestone powder is 0.0525-0.25 mm. The use of temperature-resistant powder containing sandstone particles, talcum powder, and limestone powder to prepare a modified asphalt composition can effectively fill the gaps between asphalt molecules and prevent the modified asphalt composition from deforming due to shrinkage at extremely low temperatures.
[0049] In some embodiments of the present application, the average particle size of fly ash is 0.1 μm to 100 μm. The fly ash particles have a porous honeycomb structure and a large specific surface area (800 to 10,000 cm2 measured by nitrogen adsorption method). 2 / g), which can be fully connected with SEBS molecules and asphalt molecules through the porous honeycomb structure, preventing the modified asphalt composition from deforming and shrinking at high or extremely low temperatures, thereby preventing the modified asphalt waterproofing membrane from deforming and shrinking.
[0050] In some embodiments of the present application, the average particle size of nano silicon dioxide is 1nm to 10μm. Optionally, the average particle size of nano silicon dioxide is 1nm to 5μm. Exemplarily, the average particle size of nano silicon dioxide is 20nm to 90nm, 100nm to 800nm, 1μm to 5μm. Nano silicon dioxide has a small size effect and a surface effect.
[0051] In some embodiments of the present application, the average particle size of nano-silica is 300nm, 450nm, 560nm, 600nm, 700nm, 750nm, 800nm, 1.2μm, 1.5μm, 2.0μm, 2.5μm, 2.8μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 6μm, 6.3μm, 7.0μm, 7.5μm, 8μm, 9μm, 9.6μm, or a combination of nano-silica with multiple average particle size values mentioned above.
[0052] In the embodiments of the present application, nano-silicon dioxide is added to asphalt to fill the tiny pores inside the asphalt, making the asphalt structure more compact. When deformed by external forces, this compact structure can better resist deformation. At the same time, the extremely low thermal conductivity of nano-silicon dioxide is used to improve the sensitivity of asphalt to temperature and the compactness, so that asphalt can maintain relatively stable performance at different temperatures and reduce shrinkage deformation caused by temperature changes.
[0053] In some embodiments of the present application, the nano-silica is fumed nano-silica. Fumed nano-silica includes two types: primary particles and aggregates. The average particle size of the primary particles of fumed nano-silica is 7nm to 40nm, and the average particle size of the aggregated fumed nano-silica is about 200nm to 500nm. Fumed nano-silica has a porous property, and its porosity is as high as 80% to 90%. The high porosity enables the fumed nano-silica to embed the macromolecular parts of asphalt molecules and hydrogenated styrene-butadiene block copolymers into the pores, or to entangle with the fumed nano-silica through the pores, thereby enhancing the compatibility and connectivity between the components in the modified asphalt composition, and cooperating with other components to prevent the modified asphalt composition from shrinking and deforming at low temperatures.
[0054] In some embodiments of the present application, the carbon nanotubes are multi-walled carbon nanotubes, the average diameter of the carbon nanotubes is 2nm to 20nm, and the axial length of the carbon nanotubes is 5μm to 15μm. For example, the multi-walled carbon nanotubes can be nickel-based carbon nanotubes SCC-9.
[0055] In the embodiments of the present application, carbon nanotubes are also known as buckytubes. The layers of multi-walled carbon nanotubes are composed of several to dozens of layers of coaxial circular tubes composed of hexagonally arranged carbon atoms. The layers in the multi-walled carbon nanotubes maintain a fixed distance between the layers, which is about 0.34nm. Carbon nanotubes with the above diameter and length are dispersed in the modified asphalt composition, so that the modified asphalt composition can form a three-dimensional network structure, effectively supporting the asphalt dispersion raw material made of the first component asphalt and the second asphalt component. Carbon nanotubes, with their special one-dimensional quantum structure as a modified material, have both the hardness and good flexibility of diamonds, and basically do not deform at high and low temperatures. After the carbon nanotubes are integrated into the asphalt, they can be used as supporting structural members, playing a role similar to "rebar", forming a three-dimensional network structure inside the modified asphalt composition, so that the modified asphalt composition can also be restored to its original state after being subjected to pressure. When the modified asphalt composition is subjected to deformation external forces such as tension or compression, the carbon nanotube network can effectively disperse stress and enhance the anti-deformation ability of the modified asphalt composition, thereby allowing the waterproofing roll to be repeatedly compressed, greatly extending the service life of the waterproofing roll.
[0056] In some embodiments of the present application, the aspect ratio of the carbon nanotube is 200 to 7500. The aspect ratio of the carbon nanotube is the ratio of the axial length of the carbon nanotube to the paper towel. Carbon nanotubes that meet this aspect ratio can form a suitable three-dimensional network structure with the asphalt molecules and hydrogenated styrene-butadiene block copolymer in the modified asphalt composition. Optionally, the aspect ratio of the carbon nanotube is 200, 220, 240, 280, 300, 350, 400, 500, 600, 750, 800, 910, 1000, 1200, 3000, 4000, 4500, 5000, 6000, 6300, 6670, 7000, 7200. Carbon nanotubes with an aspect ratio of 150 to 5000 are preferred.
[0057] In the embodiments of the present application, the combination of nano-silicon dioxide and carbon nanotubes has the property of making the modified asphalt composition maintain a relatively stable performance at different temperatures, reducing the shrinkage deformation caused by temperature changes. Among them, carbon nanotubes and nano-silicon dioxide are mutually dispersed systems with asphalt mastic and hydrogenated styrene-butadiene block copolymer. When the modified asphalt composition is in a high temperature environment, when the molecules of asphalt mastic and hydrogenated styrene-butadiene block copolymer and the first component asphalt and the second component asphalt are entangled and connected by heat and expand, the carbon nanotubes distributed therein utilize the three-dimensional network structure formed with the macromolecules to support each other in an interlaced manner, hindering the deformation of several molecules by heat, and the nano-silicon dioxide dispersed in the three-dimensional network structure fills the gaps between the molecules, further hindering the deformation caused by the thermal expansion of several molecules, so that the modified asphalt composition and the modified asphalt waterproofing membrane containing it can also have good dimensional stability at high temperatures (80°C). In contrast, when the modified asphalt composition is in an extremely low temperature environment, the asphalt molecules of the first component asphalt and the second component asphalt are physically entangled and connected with the hydrogenated styrene-butadiene block copolymer, so that the modified asphalt composition has good deformation performance and excellent mechanical properties. At the same time, the three-dimensional network structure formed by the carbon nanotubes and macromolecules contained in the modified asphalt composition interlaces and supports each other, hindering the first component asphalt, the second component asphalt, asphalt mastic and hydrogenated styrene-butadiene block polymer from shrinking at low temperatures. The nano-silicon dioxide dispersed in the three-dimensional network structure further supports the carbon nanotubes to prevent deformation, and hinders the macromolecules from shrinking due to cold, thereby effectively improving the dimensional stability of the modified asphalt composition and the modified asphalt waterproof membrane containing it at low temperatures.
[0058] In some embodiments of the present application, the average particle size of the fumed nano-silicon dioxide of the primary particles is 10nm to 40nm, and the fumed nano-silicon dioxide is the fumed nano-silicon dioxide of the aggregate, and the average particle size is 100nm to 500nm. Exemplarily, the average particle size of the fumed nano-silicon dioxide is 120nm, 150nm, 160nm, 180nm, 200nm, 240nm, 270nm, 300nm, 350nm, 400nm, 420nm, 450nm, 480nm.
[0059] In the embodiment of the present application, the fumed nano-silica with this particle size range has a porous characteristic. When it is compounded with carbon nanotubes with an average diameter of 2nm to 35nm, at least one end of the two ends of some carbon nanotubes along the axial direction can be extended into the pores of the fumed nano-silica, forming a material with at least one end being dumbbell-shaped. While the carbon nanotubes and the molecules of other components form a three-dimensional network structure, the dumbbell-shaped structure of the fumed nano-silica at both ends of the carbon nanotubes can further hinder the deformation of the macromolecules of other components caused by thermal expansion or cold contraction, so that the modified asphalt composition has good dimensional stability. The fumed nano-silica with a particle size smaller than this range effectively fills the pores of the three-dimensional network structure, hinders the shrinkage and deformation between molecules, and makes the modified asphalt composition and the modified asphalt waterproofing membrane containing the modified asphalt composition have good dimensional stability, thereby adapting to building waterproofing in different temperature environments.
[0060] In some embodiments of the present application, the bonding strength of asphalt mastic at 20°C is 1.4 kg / cm 2 ~1.6kg / cm 2 The frost resistance requires no cracking or detachment after hanging at -40°C for 2 hours, and an elongation of 35cm to 45cm at 25°C. In the embodiments of the present application, the asphalt mastic meeting the above requirements can enhance the flexibility and low temperature shrinkage deformation resistance of the modified asphalt composition.
[0061] In some embodiments of the present application, asphalt mastic is an asphalt mixture composed of asphalt mastic composed of asphalt, fiber stabilizer, mineral powder and a small amount of fine aggregate, which is filled with the gap of the coarse aggregate skeleton with discontinuous grading. In some embodiments, asphalt mastic is made of 8% to 10% of 1mm coarse aggregate, 25% to 30% of 200 mesh mineral powder, 45% to 60% of asphalt with a needle penetration of 60 to 110, and 2.5% to 3% of fiber stabilizer; wherein the unit of needle penetration is 1 / 10 mm. The skeleton formed by direct contact and mutual interlocking of the particles of high content coarse aggregate in the mixture directly bears the load, and this skeleton is less sensitive to temperature. The high content of mineral powder and asphalt components form a highly cohesive gel-like substance-mast, which improves the overall mechanical properties of the mixture. The effects of these two aspects make the mixture have sufficient vertical and lateral constraints, and no or only slight deformation occurs under the contraction caused by extreme low temperature or the expansion caused by high temperature. If it is compounded with other components in the modified asphalt composition, the bonding force between the components can be used to improve the anti-shrinkage deformation performance of the modified asphalt composition at extremely low temperatures. It has the characteristics of good air tightness, waterproofness, antifreeze, not easy to crack and age, and can be cold-applied at room temperature.
[0062] In the embodiment of the present application, the coarse aggregate inside the asphalt mastic (abbreviated as SMA) is mutually embedded to form a stable skeleton structure, and the asphalt mortar composed of asphalt with a needle penetration of 60 to 110 (unit is 1 / 10 mm) provides good bonding force and can resist the shear force generated from the outside. At the same time, due to the reinforcing effect of the fiber in the fiber stabilizer, the asphalt mastic has good flexibility at low temperatures and can effectively prevent cracks in the coiled material. As the amount of asphalt mastic added increases, the effect will gradually weaken.
[0063] In some embodiments of the present application, the hydrogenated styrene-butadiene block copolymer is a linear or star-shaped structure or a combination thereof, the molecular weight of the hydrogenated styrene-butadiene block copolymer is 150,000 to 450,000, and the mass content of the styrene segment in the hydrogenated styrene-butadiene block copolymer is 25% to 35%.
[0064] In the embodiments of the present application, hydrogenated styrene-butadiene block polymer (SEBS in English) is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenating polybutadiene as the middle elastic block, which combines the advantages of plastic and rubber. Hydrogenated styrene-butadiene block polymer has good weather resistance, heat resistance, compression deformation resistance and excellent mechanical properties. After hydrogenated styrene-butadiene block copolymer is incorporated into asphalt, the rheological properties of asphalt can be optimized, and asphalt can maintain good deformation resistance under different stress and temperature conditions. In an environment with large temperature fluctuations, the modified asphalt composition containing hydrogenated styrene-butadiene block polymer can effectively prevent the deformation caused by thermal expansion and contraction of the modified asphalt waterproof membrane after impregnating the polyester tire.
[0065] In the embodiments of the present application, the amount of hydrogenated styrene-butadiene block polymer added to the modified asphalt composition needs to be strictly controlled. When the amount of hydrogenated styrene-butadiene block copolymer is too little, the modified asphalt composition and the modified asphalt waterproofing membrane cannot have good flexibility. When the amount of hydrogenated styrene-butadiene block copolymer is too much, the viscosity of the modified asphalt composition is relatively large, and it is not easy to penetrate the polyester tire, so that the polyester tire cannot be fully filled by the modified asphalt composition, and it is difficult to prepare a modified asphalt waterproofing membrane that resists shrinkage deformation. In addition, adding too much hydrogenated styrene-butadiene block copolymer will increase the viscosity of the modified asphalt composition, resulting in an increase in the temperature requirement of the modified asphalt composition, and will also consume too much heat energy, increasing manufacturing costs.
[0066] In the embodiments of the present application, asphalt mastic and hydrogenated styrene-butadiene block copolymer work together with other components to play a key role in improving the tensile properties of the waterproof membrane. When faced with external tensile forces, the modified asphalt waterproof membrane can show excellent toughness and strength, is not easy to break, and provides reliable waterproof protection for buildings.
[0067] In a second aspect, the present application provides a method for preparing a modified asphalt composition, such as Figure 1 As shown, it includes: dispersing the first component asphalt and the second component asphalt according to the ratio of the modified asphalt composition, heating to 120°C to 140°C to melt the first component asphalt and the second component asphalt to obtain an asphalt dispersion raw material; adding asphalt mastic and hydrogenated styrene-butadiene block copolymer to the asphalt dispersion raw material for dispersion, and heating to 160°C to 180°C for insulation treatment to obtain a polymer asphalt dispersion; adding temperature-resistant powder and carbon nanotubes to the polymer asphalt dispersion for dispersion, and heating to 180°C to 190°C to obtain a modified asphalt composition.
[0068] In the embodiments of the present application, during the process of first adding asphalt mastic and hydrogenated styrene-butadiene block copolymer and then adding temperature-resistant powder and carbon nanotubes to the asphalt dispersion raw material, the temperature is gradually increased to allow the components to be fully mixed.
[0069] In some embodiments of the present application, 100 PHR of the first asphalt component and 60 PHR to 80 PHR of the second asphalt component can be added to a metal reactor according to the ratio of the modified asphalt composition, and stirring is maintained at 1000 rpm to 1200 rpm. The temperature is raised to 120°C to 140°C to melt the first component asphalt and the second component asphalt, thereby obtaining an asphalt dispersion raw material to serve as a carrier for other components.
[0070] In some embodiments of the present application, 4PHR to 8PHR of mastic asphalt and 3PHR to 7PHR of hydrogenated styrene-butadiene block copolymer are added to the asphalt dispersion raw material for dispersion, and the temperature is raised to 160°C to 180°C and kept for 0.5 hour to 1 hour to obtain a polymer asphalt dispersion.
[0071] In the embodiment of the present application, asphalt mastic and hydrogenated styrene-butadiene block copolymer are added to the asphalt dispersion raw material to modify the asphalt dispersion raw material, and the hydrogenated styrene-butadiene block copolymer is swollen and mixed with asphalt mastic and asphalt dispersion raw material at 160°C to 180°C. Among them, asphalt mastic has relatively low temperature requirements and is easily soluble, so it can be added first for dispersion. Then, hydrogenated styrene-butadiene block copolymer is added for swelling and mixing.
[0072] In some embodiments of the present application, 10PHR to 20PHR of temperature-resistant powder and 4PHR to 8PHR of carbon nanotubes are added to the polymer asphalt dispersion for dispersion, and the temperature is raised to 180°C to 190°C, and the rotation speed is maintained at 1000rpm to 1200rpm for shear dispersion for 1 hour to 1.5 hours to obtain a modified asphalt composition that is resistant to shrinkage deformation.
[0073] In an embodiment of the present application, temperature-resistant powder and carbon nanotubes are added to the polymer asphalt dispersion for dispersion, and the temperature is raised to 180°C to 190°C for shear dispersion for a certain period of time. The anisotropy of the carbon nanotubes in the modified asphalt composition can be increased, so that the temperature-resistant powder fills the gaps between the asphalt molecules, and is compounded with the carbon nanotubes and other components to obtain a modified asphalt composition. The anisotropic carbon nanotubes can hinder the deformation of the modified asphalt composition due to shrinkage at extremely low temperatures from multiple different directions, and can also hinder the deformation of the modified asphalt composition due to expansion at high temperatures, so that the modified asphalt waterproof membrane prepared from the modified asphalt composition has good stability, that is, good anti-deformation performance.
[0074] In some embodiments of the present application, adding the anti-temperature change powder and the carbon nanotubes to the polymer asphalt dispersion for dispersion further comprises: dispersing the anti-temperature change powder and the carbon nanotubes first. Dispersing the anti-temperature change powder and the carbon nanotubes first can make the carbon nanotubes and the anti-temperature change powder evenly distributed, and at least partially insert the two ends of the carbon nanotubes into the pores of the anti-temperature change powder to form a dumbbell-shaped structure to fill and support the gaps between the asphalt molecules and the gaps between the polyester tires, thereby preventing the polyester tires and waterproof rolls containing the modified asphalt composition from deforming under high temperature or extremely low temperature environments.
[0075] In one embodiment, the temperature-resistant powder is nano-silicon dioxide, fly ash, sandstone particles or a combination thereof, preferably gas-phase nano-silicon dioxide and fly ash.
[0076] The inventors of this application have discovered that the shrinkage and deformation of existing waterproof membranes is often caused by the fact that the polyester tire, which serves as the main tire base, is prone to shrinkage and deformation at extremely low temperatures. Conventional polyester tires are treated with a mixture of asphalt of different grades as an impregnation coating, and have poor resistance to shrinkage and deformation at extremely low temperatures.
[0077] On the third aspect, the present application provides an asphalt waterproofing roll material to solve the above-mentioned problem, comprising: a polyester base 1, the polyester base is dipped in the above-mentioned modified asphalt composition 3; a coating layer 4, at least arranged on one side of the two opposite sides of the polyester base dipped in the modified asphalt composition.
[0078] The modified asphalt waterproofing membrane of the present application has made innovations in this regard. Temperature-resistant powder, carbon nanotubes, asphalt mastic and hydrogenated styrene-butadiene block copolymer are added to the mixture formed by the first component asphalt and the second component asphalt for modification and adjustment. The synergistic effect of several components is utilized to make the polyester tire dipped in the modified asphalt composition achieve the effect of anti-deformation, thereby making the modified asphalt membrane have good anti-shrinkage deformation performance even at extremely low temperatures.
[0079] In some embodiments of the present application, based on the polyester tire per square meter, the amount of the modified asphalt composition dipped per square meter of the polyester tire is 0.4kg to 1.5kg.
[0080] In some embodiments of the present application, based on a polyester tire with a thickness of 1.5 mm and 260 g per square meter, the amount of the polyester tire dip-coated modified asphalt composition per square meter is 0.75 kg to 1.2 kg, and preferably the amount of the polyester tire dip-coated modified asphalt composition per square meter of 260 g is 0.9 kg to 1.0 kg.
[0081] In some embodiments of the present application, based on a polyester tire with a thickness of 1.2 mm and a weight of 200 g per square meter, the amount of the modified asphalt composition applied to each square meter of the polyester tire is 0.5 kg to 0.8 kg.
[0082] In some embodiments of the present application, based on a polyester tire with a thickness of 1.0 mm and 140 g per square meter, the amount of the modified asphalt composition dipped per square meter of the polyester tire is 0.4 kg to 0.6 kg.
[0083] Traditional waterproofing membranes have poor performance in terms of anti-deformation and shrinkage performance of polyester tires. However, this application uses a modified asphalt composition to modify the polyester tire by dipping it, creating a new method for preparing modified asphalt waterproofing membranes. The modified asphalt waterproofing membrane greatly improves the anti-shrinkage and deformation ability of the polyester tire body through the unique modification method of dipping the polyester tire into the modified asphalt composition. In practical applications, this means that the modified asphalt waterproofing membrane can better adapt to various complex building structures and environmental changes, reduce the risk of leakage caused by shrinkage and deformation, and provide more reliable waterproof protection for buildings.
[0084] In some embodiments of the present application, the polyester tire is a reinforced polyester tire, and the modified asphalt waterproof membrane using the reinforced polyester tire has a better effect of resisting shrinkage and deformation at low temperatures.
[0085] In the embodiments of the present application, the polyester tire, also known as polyester felt, tire base cloth, polyester fiber, is made of polyester fiber (such as polyethylene terephthalate fiber) as the main raw material. It is woven into a tire structure with a certain thickness, strength and elasticity through a textile process, has high strength and good flexibility, and the polyester fibers are interwoven to form a stable mesh structure. Optionally, the polyester tire is a composite felt of polyester felt and glass fiber mesh cloth formed by combining polyester felt and glass fiber mesh cloth.
[0086] In some embodiments of the present application, the coating layer is a coating composition composed of the following components by mass percentage: 70# asphalt, 45% to 55%; softening oil, 12% to 14%; SBS modifier, 5% to 7%; tire rubber powder, 8% to 11%; filler, 20% to 30%. The coating layer is a part of the modified asphalt waterproofing membrane, which has the function of improving the heat resistance, low temperature flexibility and impermeability of the waterproofing membrane.
[0087] In the embodiments of the present application, the coating layer, as a part of the modified asphalt waterproof membrane, has the function of improving the heat resistance, low-temperature flexibility and impermeability of the waterproof membrane.
[0088] In the embodiments of the present application, the thickness of the coating layer is 1.2 to 2 times the thickness of the polyester tire.
[0089] In some embodiments of the present application, the softening oil can be selected from one or more of 200#-300# asphalt, mineral oil, synthetic oil, and vegetable oil. At least 200#-300# asphalt purchased from Shandong Jingbo can be selected.
[0090] In the embodiment of the present application, the SBS modifier is a styrene-butadiene-styrene block copolymer, the molecular weight of which is 150,000 to 400,000, and the mass content of the styrene segment is 20% to 30%. The SBS can at least be purchased from Tianjin Lejin LG411.
[0091] In the embodiment of the present application, the filler is selected from stone powder, heavy calcium powder, fly ash or a combination thereof. The average particle size of the filler is 180 mesh to 300 mesh. At least 200 mesh stone powder of Anshan Haicheng Tianli can be selected.
[0092] In the embodiment of the present application, the tire rubber powder has an average particle size of 70-120 meshes, and at least 80-mesh tire rubber powder from Hebei Zongming can be used.
[0093] In some embodiments of the present application, the modified asphalt waterproof membrane further includes an isolation protection layer 5 , and the isolation protection layer 5 covers the surface of the coating layer 4 on one side facing away from the polyester tire 1 .
[0094] In some embodiments of the present application, the isolation protection layer 5 is made of a transparent low-density polyethylene (PE) or polypropylene (PP) material, or a film made of a composite of these two materials.
[0095] It should be noted that in actual products, the carbon nanotubes 6 are anisotropically distributed in the polyester fibers 2 of the polyester tire 1 . Figure 2 The carbon nanotubes 6 are only distributed in the horizontal direction, which is intended to illustrate the position distribution of some carbon nanotubes 6 and polyester fibers 2 in the polyester tire 1, and is not intended to limit the technical solution of this application. Nano-silicon dioxide and SEBS should be dispersed in the modified asphalt composition 3 between the polyester fibers 2. To avoid unclear structural diagrams, SEBS is Figure 2 Not shown.
[0096] In the examples of the present application, the modified asphalt waterproofing membrane has improved important properties such as preventing weight increase after immersion, oil permeability resistance and soluble matter. After being modified with the modified asphalt composition that resists shrinkage and deformation, the water resistance of the waterproofing membrane is greatly improved, and the weight change after immersion is reduced. At the same time, the content of soluble matter is effectively controlled, which means that even in a humid environment, the modified asphalt waterproofing membrane can maintain stable performance and extend its service life.
[0097] It should be noted that soluble matter refers to substances in asphalt and SBS that are soluble in trichloroethylene or carbon tetrachloride. The national standard requires that there are minimum limits on the amount of soluble matter of different thicknesses.
[0098] More importantly, in the modified asphalt waterproofing membrane of the embodiment of the present application, after being modified by a modified asphalt composition that resists shrinkage and deformation, the comprehensive performance of the modified asphalt waterproofing membrane is greatly improved, and the amount of raw materials such as asphalt added in the coating material that forms the coating layer can be appropriately reduced, thereby reducing the production cost of the coating material and improving the efficiency of the modified asphalt waterproofing membrane product, providing a more reliable waterproofing product for construction projects.
[0099] It should be noted that different regions should make corresponding adjustments according to the environment. Conventional impregnation coatings are mixed with pure asphalt, but different types of waterproof membranes have different oil permeability requirements, so the asphalt grades and proportions used will also be different. In the present application, the modified asphalt composition after the asphalt dispersion raw material is added with additives can not only play an anti-deformation effect, but also meet the oil permeability requirements of different types of waterproof membranes. At the same time, the performance of the increase in mass after immersion in water is also greatly improved, so that the waterproof effect and life of the waterproof membrane are improved. The present application breaks the previous solution that waterproof membranes can only be modified and innovated from the coating material, so that the waterproof membrane can achieve performance improvement in both the coating material and the polyester tire. The modified asphalt waterproof membrane of the present application will play a more important role and create a safer and more comfortable living or working environment for people.
[0100] It should be noted that, in general asphalt waterproofing membranes, oily substances will seep out at high temperatures. However, the modified asphalt waterproofing membrane of the present application, while using the modified asphalt composition to fill the gaps in the polyester tire, the gaps inside the asphalt molecules themselves are filled with fine particles of nano-silicon dioxide, which cooperates with the three-dimensional network structure formed by carbon nanotubes and asphalt mastic hydrogenated styrene-butadiene block copolymers, while hindering the expansion and deformation of the modified asphalt waterproofing membrane at high temperatures, can prevent the oily substances from seeping out of the modified asphalt waterproofing membrane through the nano-silicon dioxide filling its gaps and pores, and prevent water from penetrating through the modified asphalt waterproofing membrane, thereby preventing the quality of the modified asphalt waterproofing membrane from being greatly increased after being immersed in water.
[0101] In the fourth aspect, the present application provides a method for preparing a modified asphalt waterproofing membrane, comprising: impregnating a polyester base in a modified asphalt composition that resists shrinkage and deformation at a temperature of 175°C to 185°C to obtain an impregnated polyester base; and coating the coating composition on the impregnated polyester base to obtain a modified asphalt waterproofing membrane.
[0102] Exemplarily, an embodiment of the present application provides a method for preparing a modified asphalt waterproofing membrane, comprising: injecting the above-prepared anti-shrinkage deformation modified asphalt composition into a dipping pool, controlling the temperature of the anti-shrinkage deformation modified asphalt composition to be 175°C to 185°C, using a 1015mm wide 260g polyester tire to be completely soaked in the dipping pool, and then extruding it through an extrusion roller, controlling the consumption of polyester tire soaking material per square meter to be 0.9kg to 1kg, applying the SBS II 4.0 product, i.e., a coating composition containing a polymer, on the polyester tire after oil immersion and extrusion, covering it with a PE film as an isolation protective layer, rolling and compacting it with a pressure roller, cooling, trimming, rolling, and after passing the inspection and acceptance, it is a modified asphalt waterproofing membrane product. The coating composition is as described above.
[0103] In some embodiments, the production speed of the modified asphalt waterproof membrane is controlled to be 23m / min to 28m / min.
[0104] In a fifth aspect, an embodiment of the present application provides a modified asphalt composition as described above for use in modifying a polyester tire, that is, for use in preparing a modified asphalt waterproofing membrane.
[0105] The technical solution of the present application is further described below through specific examples and comparative examples. The following are the specifications, trade names or models, and available sources of some raw materials used in the examples and comparative examples. The raw material components not mentioned can all be purchased from the market:
[0106] Modified asphalt composition
[0107] The first component asphalt, 70# asphalt, has a needle penetration of 60-80; the second component asphalt, 30# asphalt, has a needle penetration of 25-40, and the unit of needle penetration is 1 / 10 mm. Nano-silicon dioxide, average particle size 1nm-100nm. Carbon nanotubes, average diameter 2nm-20nm, model: W-500, purchased from Shanghai Gaibang Industrial Co., Ltd. Asphalt mastic (hereinafter referred to as SMA), brand HY-60, its composition and content meet the requirements of asphalt mastic components, purchased from Beijing Hongya Jianye Building Materials Co., Ltd.; its adhesion at 20°C is 1.5kg / cm 2 The frost resistance requirement is no cracking or detachment after hanging at -40°C for 2 hours, and the elongation at 25°C is 36cm. Hydrogenated styrene-butadiene block copolymer (hereinafter referred to as SEBS) has a molecular weight of 150,000 to 450,000, wherein the mass content of the styrene segment is 25% to 30%.
[0108] Modified asphalt composition and preparation thereof
[0109] Example 1
[0110] The present embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with added percentages: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 6 PHR; SEBS, 5 PHR.
[0111] The modified asphalt composition resistant to shrinkage deformation is prepared by the following preparation method, comprising the following steps:
[0112] A1. Disperse 70# asphalt as the first component asphalt and 30# as the second component asphalt at a speed of 1000 rpm according to the ratio, heat to 130°C to 140°C and keep warm for 1 hour until the asphalt is completely melted to obtain asphalt dispersion raw material;
[0113] A2, adding mastic asphalt and hydrogenated styrene-butadiene block copolymer to the asphalt dispersion raw material for dispersion, and heating to 160° C. to 180° C. and keeping the temperature for 1 hour to obtain a polymer asphalt dispersion;
[0114] A3. Add nano-silicon dioxide and carbon nanotubes to the polymer asphalt dispersion, raise the temperature to 180° C. to 190° C., and shear and disperse at a speed of 1000 rpm within the temperature range for 1.5 hours to obtain a modified asphalt composition that resists shrinkage deformation.
[0115] Example 2
[0116] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 65 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 6 PHR; SEBS, 5 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0117] Example 3
[0118] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 4 PHR; SEBS, 5 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0119] Example 4
[0120] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 8 PHR; SEBS, 5 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0121] Example 5
[0122] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 6 PHR; SEBS, 3 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0123] Example 6
[0124] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 6 PHR; SEBS, 7 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0125] Example 7
[0126] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 10 PHR; carbon nanotubes, 6 PHR; SMA, 6 PHR; SEBS, 5 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0127] Example 8
[0128] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 4 PHR; SMA, 6 PHR; SEBS, 5 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0129] Example 9
[0130] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 13 PHR; carbon nanotubes, 5 PHR; SMA, 6 PHR; SEBS, 3 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0131] Example 10
[0132] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 20 PHR; carbon nanotubes, 4 PHR; SMA, 6 PHR; SEBS, 3 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0133] Embodiment 11
[0134] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 8 PHR; SMA, 6 PHR; SEBS, 3 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0135] Example 12
[0136] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 16 PHR; carbon nanotubes, 4 PHR; SMA, 6 PHR; SEBS, 3 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0137] Embodiment 13
[0138] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 13 PHR; carbon nanotubes, 4 PHR; SMA, 6 PHR; SEBS, 3 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0139] Embodiment 14
[0140] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 4 PHR; SEBS, 7 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0141] Embodiment 15
[0142] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 8 PHR; SEBS, 3 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0143] Example 16
[0144] This embodiment provides a modified asphalt composition that resists shrinkage deformation, which is prepared from the following raw materials with the following percentage additions: first component asphalt, 100 PHR; second component asphalt, 70 PHR; nano-silicon dioxide, 15 PHR; carbon nanotubes, 6 PHR; SMA, 8 PHR; SEBS, 7 PHR. The preparation method of the modified asphalt composition that resists shrinkage deformation is the same as that of Example 1.
[0145] Comparative Example 1
[0146] This comparative example provides an asphalt mixed oil, which is different from Example 1 in that only equal amounts of 70# asphalt and 30# asphalt are added, and other components in the modified asphalt composition are not added. The preparation method of the asphalt mixed oil includes: mixing 70# asphalt and 30# asphalt according to the ratio, stirring the mixture at a speed of 1000 rpm, heating the mixture to 130°C to 140°C, and then keeping the temperature for 1 hour until the asphalt is completely melted, and heating the mixture to 180°C to 190°C to obtain the asphalt mixed oil.
[0147] Comparative Example 2
[0148] This comparative example provides a modified asphalt composition, which differs from Example 1 in that only equal amounts of 70# asphalt, 30# asphalt, SEBS, nano-silicon dioxide, and carbon nanotubes are added, i.e., 6PHR SMA is not added. The preparation method is the same as Example 1, except that 6PHR SMA is not added.
[0149] Comparative Example 3
[0150] This comparative example provides a modified asphalt composition, which differs from Example 1 in that only equal amounts of 70# asphalt, 30# asphalt, SMA, nano-silicon dioxide, and carbon nanotubes are added, i.e., 5PHR of SEBS is not added. The preparation method is the same as that of Example 1, except that 5PHR of SEBS is not added.
[0151] Comparative Example 4
[0152] This comparative example provides a modified asphalt composition, which differs from Example 1 in that only equal amounts of 70# asphalt, 30# asphalt, SMA, and carbon nanotubes are added, i.e., 15 PHR of nano-silicon dioxide is not added. The preparation method is the same as that of Example 1, except that 15 PHR of nano-silicon dioxide is not added.
[0153] Comparative Example 5
[0154] This comparative example provides a modified asphalt composition, which differs from Example 1 in that only equal amounts of 70# asphalt, 30# asphalt, SMA, SEBS, and nano-silicon dioxide are added, i.e., 6PHR carbon nanotubes are not added. The preparation method is the same as Example 1, except that 6PHR carbon nanotubes are not added.
[0155] Coating composition
[0156] The coating composition is a SBS II 4.0 product, and the coating composition is composed of the following components in percentage by mass: 70# asphalt, 50%; softening oil, 13%; SBS modifier, 6%; tire rubber powder, 9%; filler, 22%; wherein, softening oil: 200#~300# asphalt, purchased from Shandong Jingbo Petrochemical Co., Ltd.; SBS, LG411, purchased from Tianjin LG Botian Chemical Co., Ltd.; tire rubber powder, 80 mesh, purchased from Hebei Zongming; filler, 200 mesh stone powder, purchased from Anshan Haicheng Tianli.
[0157] Coating layer
[0158] The coating layer is formed by coating with the coating composition of the above-mentioned SBS II 4.0 product, with a coating thickness of 2.5 mm, and is applied to the modified asphalt waterproofing membrane prepared from the modified asphalt composition or asphalt mixed oil of Examples 1-16 and Comparative Examples 1-5.
[0159] Preparation of modified asphalt waterproofing membrane
[0160] The modified asphalt compositions of Examples 1-16 and the asphalt mixed oil and modified asphalt compositions of Comparative Examples 1-5 were respectively put into corresponding dipping pools, and the temperature thereof was controlled to be 180°C ± 2°C. A polyester tire (thickness of 1.5mm, 260g per square meter) with a width of 1015mm was completely dipped in the modified asphalt compositions of Examples 1-16 and the asphalt mixed oil and modified asphalt compositions of Comparative Examples 1-5 in the dipping pool, and then extruded by extrusion rollers, respectively, and the dipping material consumption per square meter of the polyester tire was controlled to be 1kg. Then, the polymer coating composition of the SBS II 4.0 product was coated on the polyester tire after dipping and extrusion, and the coating thickness was 2.5mm. After film coating (PE film), roller knurling and compaction, cooling, trimming, rolling, and inspection and acceptance, the modified asphalt waterproofing membrane was prepared.
[0161] Comparative Example 6
[0162] This comparative example provides a modified asphalt waterproofing membrane, which is prepared by using the modified asphalt composition of Example 1. The difference between the modified asphalt waterproofing membrane prepared by Example 1 and the modified asphalt waterproofing membrane of Example 6 is that: in the modified waterproofing membrane of Comparative Example 6, the polyester tire is not dipped in the modified asphalt composition of Example 1, but the modified asphalt composition of Example 1 is evenly coated on the two sides of the polyester tire with the same thickness and opposite to each other in the thickness direction, and the coating thickness is 2.5mm. Then, the polymer coating composition of the SBS II 4.0 product is coated on the polyester tire after oil immersion and extrusion, and the coating thickness is 2.5mm. After film coating (PE film), roller knurling and compaction, cooling, trimming, rolling, and inspection and acceptance, the modified asphalt waterproofing membrane is prepared.
[0163] Performance Testing
[0164] The modified asphalt waterproof membranes prepared in Examples 1-16 and Comparative Examples 1-6 were subjected to performance tests, and the width of the membranes after production of the polyester base with a width of 1015 mm was recorded in the test. The waterproof membrane samples prepared in Examples 1-16 and Comparative Examples 1-6 were placed under standard environmental conditions (temperature of 23°C ± 2°C, relative humidity of 50% ± 5%) for 24 hours to reach equilibrium, and then the following items were tested and the results recorded.
[0165] 1. Deformation test
[0166] The deformation test of modified asphalt waterproof membrane adopts the national standard GB / T 328-2007 "Test method for building waterproof membrane" Part 8 for sample preparation and testing.
[0167] 2. Aging test under high temperature environment
[0168] The aging test of modified asphalt waterproof membrane in high temperature environment is carried out in accordance with the national standard GB 18242-2008 "Elastomer modified asphalt waterproof membrane" 6.13.4.3 dimensional change rate for sample preparation and testing.
[0169] 3. Low temperature shrinkage performance test
[0170] Methods for low temperature shrinkage testing include:
[0171] 3.1 Sample preparation: Select representative modified asphalt waterproofing membrane samples, the size of which should meet the requirements of relevant standards. As mentioned above, before testing, the modified asphalt waterproofing membrane samples prepared in Examples 1-16 and Comparative Examples 1-6 were placed under standard environmental conditions (temperature of 23°C ± 2°C, relative humidity of 50% ± 5%) for 24 hours to reach equilibrium.
[0172] 3.2 Low temperature treatment: Place the samples prepared in Examples 1-16 and Comparative Examples 1-6 into a low temperature environment test box, set the required low temperature temperature to -28°C and -38°C, respectively, and keep the samples in the above low temperature environment for 48 hours to ensure that the samples are fully treated with low temperature.
[0173] 3.3 Dimension measurement: Use accurate measuring tools (such as vernier calipers) to measure the width of the waterproof membrane before and after low temperature treatment. When measuring, multiple measurements should be made at different locations of the test sample, and the average value should be taken to improve the accuracy of the measurement.
[0174] 3.4 Calculate the shrinkage rate: Based on the measurement results, calculate the shrinkage of the waterproof membrane in a low temperature environment. The calculation formula for shrinkage is:
[0175] Shrinkage amount = average size of the test sample before low-temperature treatment - average size of the test sample after low-temperature treatment.
[0176] The performance test results of the modified asphalt waterproof membranes of Examples 1-16 and Comparative Examples 1-6 are recorded in Table 1 below:
[0177] Table 1
[0178]
[0179] By comparing the raw material composition and content ratio of the modified asphalt waterproof membrane of Examples 1-16 and Comparative Examples 1-6, and the test results of various properties in Table 1, it can be concluded that:
[0180] The modified asphalt waterproofing membranes prepared by the modified asphalt compositions of Examples 1-16 of the present application have a dimensional change rate of 0% under a lateral tensile force of about 1200N / 50mm, indicating that the dimensional stability of the modified asphalt waterproofing membranes is good. The modified asphalt waterproofing membranes prepared by the modified asphalt compositions of Comparative Examples 1-6 have a dimensional change rate of 0.12% to 0.67% under a lateral tensile force of about 1100N / 50mm, indicating that the dimensional stability of the modified asphalt waterproofing membranes is relatively poor. Among them, the dimensional change rate of the modified asphalt waterproofing membrane of Comparative Example 1 containing only asphalt mixed oil of 70# asphalt and 30# asphalt is the largest, reaching 0.67%, indicating that the dimensional stability of the waterproofing membranes that do not use the modified asphalt composition of the present application after being subjected to force is poor, and it also indicates that the modified asphalt composition of the embodiments of the present application can effectively improve the dimensional stability of the waterproofing membranes under force. The modified asphalt waterproofing membrane prepared by the modified asphalt composition of comparative example 2 without SMA and comparative example 5 without carbon nanotubes has a relatively poor dimensional stability compared with the dimensional stability of the waterproofing membrane prepared by the modified asphalt composition of Examples 1-16, and the dimensional change rate is 0.12%, indicating that SMA and carbon nanotubes are both necessary components for the modified asphalt composition, and the lack of one will make the stress resistance and deformation resistance of the modified asphalt waterproofing membrane worse. The waterproofing membrane prepared by the modified asphalt composition of comparative example 3 without SEBS and comparative example 4 without nano-silicon dioxide has a poor dimensional stability under a lateral tensile force of about 1100N / 50mm compared with the dimensional stability of the waterproofing membrane prepared by the modified asphalt composition of Examples 1-16, and the dimensional change rate is 0.20% and 0.16% respectively, and the dimensional stability of the modified asphalt waterproofing membrane prepared by the modified asphalt composition of comparative examples 2 and 5 is also poor, indicating that SEBS and nano-silicon dioxide are also essential components for the modified asphalt composition, and have a relatively large impact on its stress resistance and deformation resistance. Comparative Example 6: A modified waterproof asphalt membrane prepared by coating the modified asphalt composition of Example 1 on both side surfaces of a polyester tire in the thickness direction has a dimensional change rate of up to 0.59% under a lateral tensile force of about 1100 N / 50 mm. Its dimensional stability is significantly lower than that of the modified asphalt waterproof membrane prepared by dipping the modified asphalt composition of Comparative Examples 2-5 on a polyester tire, and also lower than that of the modified asphalt waterproof membrane prepared by dipping the modified asphalt composition of Examples 1-16 on a polyester tire. This also indicates that dipping the modified asphalt composition onto a polyester tire is necessary to effectively improve the modified asphalt waterproof membrane.
[0181] Comparing the modified asphalt waterproofing membranes prepared by the modified asphalt compositions of Example 1 and Example 2, the amount of 30# asphalt used is reduced, but the shrinkage rates of the two at -28°C are 0.79% and 0.59%, respectively, which are significantly lower than the shrinkage rates of 1.29% to 5.38% of the modified asphalt waterproofing membranes of Comparative Examples 1-6 at -28°C, indicating that the width shrinkage performance of the modified asphalt waterproofing membranes at -28°C is not much different; the shrinkage rates at -38°C are 2.07% and 1.88%, respectively, which are significantly lower than the shrinkage rates of 2.88% to 7.57% of the modified asphalt waterproofing membranes of Comparative Examples 1-6 at -38°C, indicating that the width shrinkage performance of the modified asphalt waterproofing membranes at -38°C is not much different. These two shrinkage properties under extremely low temperatures indicate that the addition amount of 30# asphalt has little effect on the deformation resistance of the modified asphalt waterproofing membrane.
[0182] Comparing the modified asphalt waterproofing membranes prepared from the modified asphalt compositions of Example 3, Example 1 and Example 4, the amount of SMA gradually increased, and the shrinkage rates at -28°C were 0.79%, 0.79%, and 0%, respectively, and the shrinkage rates at -38°C were 2.48%, 2.08%, and 1.48%, respectively, indicating that with the increase in the amount of SMA, the effect of the modified asphalt waterproofing membrane in resisting shrinkage deformation at extreme low temperatures is weakened. And compared with the modified asphalt waterproofing membranes of Comparative Examples 1-6, the shrinkage rates of 1.29% to 5.38% at -28°C and 2.88% to 7.57% at -38°C are still significantly reduced.
[0183] Comparing the modified asphalt waterproofing membranes prepared from the modified asphalt compositions of Example 5, Example 1 and Example 6, the amount of SEBS gradually increased, and the shrinkage rates at -28°C were 0%, 0.79%, and 1.09%, respectively, and the shrinkage rates at -38°C were 0.39%, 2.08%, and 2.78%, respectively, indicating that with the increase in the amount of SEBS, the effect of the modified asphalt waterproofing membrane in resisting shrinkage deformation is reduced. This is because excessive addition of SEBS will increase the viscosity of the modified asphalt composition, resulting in an increase in the temperature requirement for the modified asphalt composition to infiltrate the polyester tire, making it difficult to penetrate the tire base, and consuming more heat energy, increasing costs. However, compared with the shrinkage rates of 1.29% to 5.38% at -28°C and 2.88% to 7.57% at -38°C of the modified asphalt waterproofing membranes of Comparative Examples 1-6, they are still significantly reduced.
[0184] Comparing the modified asphalt waterproofing membranes prepared by the modified asphalt compositions of Example 1 and Example 7, the amount of nanosilicon dioxide in the modified asphalt waterproofing membrane prepared by Example 7 is reduced, and its shrinkage rates at -28°C and -38°C are 1.19% and 2.48%, respectively, which are increased compared to the shrinkage rates of 0.79% and 2.08% at -28°C and -38°C, respectively, of the modified asphalt waterproofing membrane prepared by Example 1, indicating that the reduction in the amount of nanosilicon dioxide will lead to a decrease in the ability of the waterproofing membrane to resist shrinkage deformation at extremely low temperatures. Therefore, it is necessary to add nanosilicon dioxide within a limited amount range.
[0185] Comparing the modified asphalt waterproofing membranes prepared by the modified asphalt compositions of Example 1 and Example 8, the amount of carbon nanotubes used in the modified asphalt waterproofing membrane prepared by Example 8 is reduced, and its shrinkage rates at -28°C and -38°C are 0.69% and 1.78%, respectively, which are smaller than the shrinkage rates of 0.79% and 2.08% of the modified asphalt waterproofing membrane prepared by Example 1 at -28°C and -38°C, respectively, indicating that the appropriate reduction in the amount of nano-silicon dioxide will enhance the ability of the waterproofing membrane to resist shrinkage deformation at extreme low temperatures to a certain extent, but the increase is small. Therefore, it is necessary to add a limited amount of carbon nanotubes.
[0186] Comparing the modified asphalt waterproofing membranes prepared from the modified asphalt compositions of Example 1, Example 9 and Example 10, the modified asphalt waterproofing membrane prepared from the modified asphalt composition of Example 9 has a reduced amount of SEBS and nano-silicon dioxide, and its shrinkage rates at -28°C and -38°C are 0.49% and 1.68%, respectively; the modified asphalt waterproofing membrane prepared from the modified asphalt composition of Example 10 has a reduced amount of SEBS and an increased amount of fumed nano-silicon dioxide, and its shrinkage rates at -28°C and -38°C are 0% and 0%, respectively. %; Compared with the modified asphalt waterproof membrane prepared in Example 1, the shrinkage rates of the modified asphalt waterproof membranes prepared in Examples 9 and 10 at extremely low temperatures are significantly reduced, and the modified asphalt waterproof membrane prepared in Example 10 has no shrinkage deformation at extremely low temperatures of -28°C and -38°C, indicating that on the basis of a suitable amount of carbon nanotubes, an appropriate combination of reducing the amounts of nano-silicon dioxide and SEBS and increasing the amount of nano-silicon dioxide can significantly improve the anti-shrinkage deformation performance of the modified asphalt waterproof membrane at extremely low temperatures of -28°C and -38°C.
[0187] Comparing the modified asphalt waterproofing membranes prepared by the modified asphalt compositions of Example 5 and Example 11, the amount of carbon nanotubes in the modified asphalt waterproofing membrane prepared by Example 11 is increased, and its shrinkage rates at -28°C and -38°C are 0% and 1.28%, respectively. Compared with the modified asphalt waterproofing membrane prepared by Example 5, the modified asphalt waterproofing membrane prepared by Example 11 has unchanged anti-shrinkage deformation performance at -28°C, and only the anti-shrinkage deformation performance at -38°C decreases, indicating that excessive amount of carbon nanotubes will also affect the anti-shrinkage deformation performance of the modified asphalt waterproofing membrane.
[0188] Comparing the modified asphalt waterproofing membranes prepared from the modified asphalt compositions of Examples 12 and 13, the amounts of SEBS and carbon nanotubes are reduced, but the amount of nano-silicon dioxide in the modified asphalt waterproofing membrane prepared in Example 13 is increased compared with Example 12. The shrinkage rates of the modified asphalt waterproofing membrane prepared in Example 12 at -28°C and -38°C are 0% and 0.29%, respectively, while the shrinkage rates of the modified asphalt waterproofing membrane prepared in Example 13 at -28°C and -38°C are 0% and 1.08%, respectively; this indicates that reducing the amounts of nano-silicon dioxide and SEBS on the basis of reducing the carbon nanotube content will result in the modified asphalt waterproofing membrane having unchanged anti-shrinkage deformation ability at -28°C, while its anti-shrinkage deformation performance at an extremely low temperature of -38°C is reduced.
[0189] Comparing the modified asphalt waterproof membranes prepared from the modified asphalt compositions of Examples 14 to 16, compared with the modified asphalt waterproof membrane prepared in Example 14, the amount of SMA in the modified asphalt waterproof membrane prepared in Example 16 is increased, and the shrinkage rates of the modified asphalt waterproof membrane prepared in Example 16 at -28°C and -38°C are 1.49% and 2.87%, respectively, which are increased compared with the shrinkage rates of the modified asphalt waterproof membrane prepared in Example 14 at -28°C and -38°C, which are 0.99% and 2.58%, respectively. This indicates that on the basis of a higher amount of SEBS, continuing to increase the amount of SMA will lead to a decrease in the anti-shrinkage deformation performance of the modified asphalt waterproof membrane at extremely low temperatures of -28°C and -38°C. Compared with the modified asphalt waterproof membrane prepared in Example 16 and its shrinkage rate at -28°C and -38°C, the amount of SEBS in the modified asphalt waterproof membrane prepared in Example 15 is reduced, and the shrinkage rates of the modified asphalt waterproof membrane prepared in Example 15 at -28°C and -38°C are reduced to 0% and 0.98%, respectively, indicating that on the basis of having a higher SMA content, appropriately reducing SEBS can improve the anti-shrinkage deformation performance of the modified asphalt waterproof membrane at extremely low temperatures of -28°C and -38°C.
[0190] Among them, the modified asphalt waterproofing membranes prepared from the modified asphalt compositions of Examples 5, 10, 12 and 15 have better shrinkage and deformation resistance at extremely low temperatures of -28°C and -38°C. In particular, the modified asphalt waterproofing membrane prepared from the modified asphalt composition of Example 10 has a shrinkage rate of 0% at extremely low temperatures of -28°C and -38°C, and has the best shrinkage and deformation resistance, while the modified asphalt waterproofing membrane prepared from Example 12 has the second best shrinkage resistance.
[0191] This application creatively adds nano-silicon dioxide, carbon nanotubes, mastic asphalt and hydrogenated styrene-butadiene block copolymer to the asphalt dispersion raw material to obtain a polyester-based impregnation coating, namely a modified asphalt composition, and uses it to prepare modified asphalt waterproofing membranes, which significantly improves the dimensional stability of modified asphalt waterproofing membranes. Whether in hot summer or cold winter, the modified asphalt waterproofing membrane can maintain a stable size and will not deform significantly due to temperature changes, providing reliable waterproof protection for buildings. At the same time, in terms of deformation resistance and low-temperature shrinkage ability, the effect is also very significant. The dimensional deformation rate of the modified asphalt waterproofing membrane is 0% under a lateral tensile force of about 1200N / 50mm.
[0192] The above is only a specific implementation method of the present application. Those skilled in the art can clearly understand that for the convenience and simplicity of description, the specific working process described above can refer to the corresponding process in the aforementioned method embodiment, and will not be repeated here. It should be understood that the protection scope of the present application is not limited to this. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application.
Claims
1. A modified asphalt composition, characterized in that: Made from the following raw materials with percentage addition: First component asphalt, 100PHR; The second component is asphalt, 60PHR~80PHR; Temperature-resistant powder, 10PHR~20PHR; Carbon nanotubes, 4PHR~8PHR; Asphalt mastic, 4PHR~8PHR; Hydrogenated styrene-butadiene block copolymer, 3PHR~7PHR.
2. The modified asphalt composition according to claim 1, characterized in that: Meet at least one of the following requirements: The first component asphalt is selected from asphalt with a needle penetration of 60 to 110, and the second component asphalt is selected from asphalt with a needle penetration of 0 to 40, wherein the unit of needle penetration is 1 / 10 mm; The temperature-resistant powder is selected from one or a combination of nano silicon dioxide, sandstone particles, talcum powder, limestone powder, and fly ash; The adhesive force of the asphalt mastic at 20°C is 1.4 kg / cm 2 ~1.6kg / cm 2 The frost resistance requires no cracking or detachment when hung at -40℃ for 2 hours, and the elongation at 25℃ is 35cm~45cm.
3. The modified asphalt composition according to claim 2, characterized in that: Meet any one of the following requirements: The average particle size of the sandstone particles, talcum powder and limestone powder is 0.0525-0.25 mm; The average particle size of the fly ash is 0.1 μm to 100 μm; The average particle size of the nano silicon dioxide is 1 nm to 10 μm; The nano silicon dioxide is gas phase nano silicon dioxide; The average particle size of the gas-phase nano-silicon dioxide is 1 nm to 1 μm.
4. The modified asphalt composition according to claim 1, characterized in that: Meet any one of the following requirements: The carbon nanotubes are multi-walled carbon nanotubes, the average diameter of the carbon nanotubes is 2nm to 20nm, and the axial length of the carbon nanotubes is 5μm to 15μm; The aspect ratio of the carbon nanotubes is 140 to 7500; The hydrogenated styrene-butadiene block copolymer is a linear or star-shaped structure or a combination thereof, the molecular weight of the hydrogenated styrene-butadiene block copolymer is 150,000-450,000, and the mass content of the styrene segment in the hydrogenated styrene-butadiene block copolymer is 25%-35%.
5. The modified asphalt composition according to claim 1, characterized in that: The asphalt mastic is prepared from 8% to 10% of 1 mm coarse aggregate, 25% to 30% of 200 mesh mineral powder, 45% to 60% of asphalt with a needle penetration of 60 to 110, and 2.5% to 3% of a fiber stabilizer; wherein the unit of the needle penetration is 1 / 10 mm.
6. The method for preparing the modified asphalt composition according to any one of claims 1 to 5, characterized in that: include: According to the ratio of the modified asphalt composition, the first component asphalt and the second component asphalt are dispersed, and the temperature is raised to 120° C. to 140° C. to melt the first component asphalt and the second component asphalt to obtain an asphalt dispersion raw material; Adding mastic asphalt and hydrogenated styrene-butadiene block copolymer to the asphalt dispersion raw material for dispersion, and heating to 160°C to 180°C for insulation treatment to obtain polymer asphalt dispersion; Adding temperature-resistant powder and carbon nanotubes into polymer asphalt dispersion to disperse the mixture, heating the mixture to 180° C. to 190° C., and obtaining a modified asphalt composition.
7. A modified asphalt waterproofing membrane, characterized in that: include: A polyester tire, wherein the polyester tire is dipped in the modified asphalt composition according to any one of claims 1 to 5; The coating layer is arranged on at least one of the two opposite surfaces of the polyester tire phase dipped in the modified asphalt composition.
8. The modified asphalt waterproofing membrane according to claim 7, characterized in that: Meet at least one of the following requirements: Based on the polyester tire per square meter, the amount of the modified asphalt composition applied to the polyester tire per square meter is 0.4kg to 1.5kg; The coating layer is formed by coating a coating composition of the following components by weight: 70# asphalt, 45% to 55%; softening oil, 12% to 14%; SBS modifier, 5% to 7%; tire rubber powder, 8% to 11%; filler, 20% to 30%; The modified asphalt waterproofing coiled material further comprises an isolation protection layer, and the isolation protection layer covers the surface of the modified material layer on one side away from the polyester base.
9. The modified asphalt waterproofing membrane according to claim 8, characterized in that: Meet at least one of the following requirements: The softening oil is one or more of 200#-300# asphalt, mineral oil, synthetic oil, and vegetable oil; The SBS modifier is a styrene-butadiene-styrene block copolymer, the molecular weight of which is 150,000 to 400,000, and the mass content of the styrene chain segment is 20% to 30%; The average particle size of the tire rubber powder is 70 mesh to 120 mesh; The filler is selected from one or more of stone powder, heavy calcium powder and fly ash; The average particle size of the filler is 180 meshes to 300 meshes.
10. Use of the modified asphalt composition according to any one of claims 1 to 5 in the preparation of modified asphalt waterproofing membrane.
Citation Information
Patent Citations
High and low temperature resistant and super anti-deformation waterproof roll
CN103753882A
Modified asphalt sizing material and low heat accumulation type waterproof roll prepared from same
CN113858740A
Low-temperature-resistant self-adhesive polymer modified asphalt waterproof coiled material and preparation method thereof
CN116463072A
Hard SBS modified asphalt waterproof coiled material and preparation process thereof
CN116872583A
Modified asphalt mixture and preparation method thereof
CN117164282A